FRIZZY PANICLE drives supernumerary spikelets in bread wheat - Dobrovolskaya, Oxana; Pont, Caroline; Sibout, Richard; Martinek, Petr; Badaeva, Ekaterina; Murat, Florent; Chosson, Audrey; Watanabe, Nobuyoshi; Prat, Elisa; Gautier, Nadine; Gautier, Véronique; Poncet, Charles; et al. (Plant physiology, 2015)
Bread wheat (Triticum aestivum) inflorescences, or spikes, are characteristically unbranched and normally bear one spikelet per rachis node. Wheat mutants on which supernumerary spikelets (SSs) develop are particularly useful resources for work towards understanding the genetic mechanisms underlying wheat inflorescence architecture and, ultimately, yield components. Here, we report the characterization of genetically unrelated mutants leading to the identification of the wheat FRIZZY PANICLE (FZP) gene, encoding a member of the APETALA2/Ethylene Response Factor transcription factor family, which drives the SS trait in bread wheat. Structural and functional characterization of the three wheat FZP homoeologous genes (WFZP) revealed that coding mutations of WFZP-D cause the SS phenotype, with the most severe effect when WFZP-D lesions are combined with a frameshift mutation in WFZP-A. We provide WFZP-based resources that may be useful for genetic manipulations with the aim of improving bread wheat yield by increasing grain number.
Keywords: pšenice; Frameshift Mutation; Triticum; genetické lokusy; květy; Genetic Loci; rostlinné geny; posunová mutace; Flowers; Genes, Plant; Phenotype; fenotyp